International organizations and the future of education assistance - Stephen P. Heyneman; Bommi Lee (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Education began to be included as a component of foreign assistance in the early 1960s as it is a principal ingredient of development. A number of multilateral and bilateral agencies were established around this time to implement various types of aid programmes; however, their effectiveness is constantly being questioned and challenged due to a variety of problems. This paper reviews the past and current activities of bilateral, multilateral organizations and private donors in education aid, examines their effectiveness, discusses major problems in implementing educational programmes and suggests ways to improve aid in education.
Keywords: I25; 330; education; foreign aid; effectiveness; multilateral; bilateral; ODA; Entwicklungshilfe; Bilaterale Entwicklungshilfe; Bildung; Internationale Organisation